Religious education in the years of the great reforms with Voronezh diocesan girl’s college as an example - Dmitriy Grechushkin (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2019)
The issue of improving education of the clergy by the mid-19th century was raised not only in state and synodal institutions, but was also vividly discussed in secular and church-related press. The great reforms undertaken by emperor Alexander II implied qualitative changes in the system of education of the clergy and their children. The new statute of theological seminaries and colleges of 1867 was very positively evaluated by the clergy and teachers, the main reason for which was the increased funding of educational institutions. However, despite the eff orts of the state to strengthen and modernise religious education, seminaries and colleges were in the acute need of suffi cient fi nancial support, whereas the state was not able to provide it under the current circumstances. This article aims to show how religious education was developing in the period of domestic reforms with Voronezh diocesan girls’ college. It studies the work of priests and laymen of Voronezh diocese in organising the diocesan college for girls in 1865 as well as the education process and everyday life of the fi rst dicesan educational institution for daughters of the clergy in the 1860s and 1870s. Using archival data, periodicals and published sources, the article describes the performance of the students, regulations of their everyday life, traits of their religious and moral state. A prominent event which demonstrated positive material change in the girls’ college was the construction and consecration of the house church with the acquisition of all necessary utensils. The article concludes that the changes that took place in religious education in the course of the reforms had undoubtedly positive results, but the liberal character of the changes had created grounds for the future systemic problems.